1996
DOI: 10.1007/bf01403705
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's disease due to a giant pituitary adenoma in early infancy: CT and MRI features

Abstract: We report the case of a 12-month-old girl presenting with diabetes insipidus and Cushing s disease. Brain magnetic resonance imaging (MRI) demonstrated a large tumour arising from the sella turcica, extending up to the foramen of Monro and invading the cavernous sinuses. Surgery was performed to remove the suprasellar part of the tumour, and histology revealed an adrenocorticotrophin (ACTH) secreting pituitary adenoma. This entity is very rare in this age group and the MRI features have not previously been des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In addition, based on the description in the reports, it was considered that three further cases probably represented PitB [13, 14, 17]. The clinical presentations and tumor histopathology of each PitB were strikingly similar, but the main predisposing genetic factors were not known.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on the description in the reports, it was considered that three further cases probably represented PitB [13, 14, 17]. The clinical presentations and tumor histopathology of each PitB were strikingly similar, but the main predisposing genetic factors were not known.…”
Section: Introductionmentioning
confidence: 99%
“…This observational study comprised a multi-institutional cohort of 17 patients with pituitary blastoma: updating 14 previously described cases (1)(2)(3)(4)(20)(21)(22)(23)(24)(25)(26)(27)(28) and fully characterizing three additional cases (16)(17)(18). Cases were identified by ongoing literature review, inquiries to leading pituitary experts and case referrals.…”
Section: Design and Study Cohortmentioning
confidence: 99%
“…Since the reports by Sahakitrungruang et al (1 case) and de Kock et al (13 cases), three additional cases of pituitary blastoma have been thoroughly investigated (1)(2)(3)(4)(16)(17)(18)(20)(21)(22)(23)(24)(25)(26)(27)(28). In 2010, Salunke et al reported a 2-month-old female with Cushingoid stigmata since birth, ophthalmoplegia, hemiparesis, and a pituitary tumor diagnosed as a "congenital immature teratoma" (Case 17; Table 1) (30,31); the pathology on review was consistent with pituitary blastoma (16).…”
Section: Recently Investigated Cases Of Pituitary Blastomamentioning
confidence: 99%
“…No additional hormone overproduction was documented. Maeder et al [15]presented the CT and MRT findings of a 12-month-old girl with a large tumor arising from the sella turcica. The histology revealed an ACTH-secreting pituitary adenoma.…”
Section: Discussionmentioning
confidence: 99%